2021
DOI: 10.1111/cpr.13091
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence suggesting the persistence of residual SARS‐CoV‐2 and immune responses in the placentas of pregnant patients recovered from COVID‐19

Abstract: Objectives Recent studies have shown the presence of SARS‐CoV‐2 in the tissues of clinically recovered patients and persistent immune symptoms in discharged patients for up to several months. Pregnant patients were shown to be a high‐risk group for COVID‐19. Based on these findings, we assessed SARS‐CoV‐2 nucleic acid and protein retention in the placentas of pregnant women who had fully recovered from COVID‐19 and cytokine fluctuations in maternal and foetal tissues. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
(130 reference statements)
0
18
0
1
Order By: Relevance
“…20 21 Similarly, viral remnants such as mRNA or proteins, or even subdetectable levels of virus, could promote a persistent immune response which results in pain and other symptoms typically associated with acute infections. 22 Treatment associated chronic pain Vaccine reactions-Vaccines are designed to induce an immune response. After entering the body, antigen derived (pathogen associated) and host derived (damage associated) molecular patterns bind to pattern recognition receptors such as toll-like receptors found on circulating immune and stromal cells.…”
Section: Continuedmentioning
confidence: 99%
“…20 21 Similarly, viral remnants such as mRNA or proteins, or even subdetectable levels of virus, could promote a persistent immune response which results in pain and other symptoms typically associated with acute infections. 22 Treatment associated chronic pain Vaccine reactions-Vaccines are designed to induce an immune response. After entering the body, antigen derived (pathogen associated) and host derived (damage associated) molecular patterns bind to pattern recognition receptors such as toll-like receptors found on circulating immune and stromal cells.…”
Section: Continuedmentioning
confidence: 99%
“…Additionally, Wu et al ( 45 ) reported that there was increased CD14+ macrophage infiltration, interferon-γ induced protein 10 (IP-10) and monocyte induced by gamma interferon (MIG) cytokines expression in term placenta from pregnant women recovering from COVID-19. The increased production of these types of chemokines within the local inflammatory lesions can induce a Th1-mediated antiviral immune response, leading to macrophage recruitment and activation for virus clearance ( 45 ). Another key finding was the reduction of plasma IL-12 secretion in pregnant patients who had recovered, indicating the activation of anti-inflammatory response might have already occurred during infection ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the COVID-19 placentas, some studies observed elevated IL-5 levels as well as decreased IL-7 and TNF-related apoptosis-inducing ligand levels. In particular, the level of IFN-γ was higher in placentas that tested positive for both viral nucleic acids and proteins relative to placentas that tested positive only for the viral proteins ( 46 ). However, significantly higher levels of IL-2, IL-6, TNF-α, and IFN-γ were found in the pregnant women with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 94%